Understanding The Difficulties and Solutions in Speaking English Among Indonesian University Students: Case Study of ABC University - Basir, Achmad (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
This study explores the factors influencing English speaking proficiency among university students in Indonesia, specifically at ABC University. Despite English being a crucial part of the national curriculum, many students still face challenges in speaking the language fluently and confidently. The study identifies several key barriers to speaking proficiency, including psychological factors such as anxiety and lack of self-confidence, as well as linguistic challenges related to vocabulary limitations, pronunciation difficulties, and grammatical uncertainties. These barriers hinder students' ability to actively participate in speaking activities and limit their overall language development. However, the study also highlights proactive strategies employed by students to improve their speaking skills, including peer practice, media engagement, the use of language learning apps, and participation in English clubs. The findings suggest that addressing both psychological and linguistic barriers through targeted interventions, such as emotional skills training and increased speaking practice opportunities, is essential for enhancing English speaking proficiency. Additionally, fostering supportive classroom environments and incorporating technology-driven learning tools can further support students' language acquisition. This study contributes to the growing body of research on English language learning in Indonesia and provides practical recommendations for improving speaking skills in higher education contexts.